KARAKTERISASI TERMAL PEB U-7Mo/Al SEBAGAI BAHAN BAKAR REAKTOR RISET - Nisa, Sayyidatun; Saputri, Ariyanti; Indaryati, Sutri; Noviarty, Noviarty; Supardjo; Ginting, Aslina Br. (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
UMo/Al-based fuel is a candidate for research reactor fuel and as an alternative to U3Si2/Al fuel. This is because the UMo/Al alloy has a higher uranium density of 16.4 g/cm3 compared to U3Si2/Al of 12.2 g/cm3. In addition, the UMo alloy has a low neutron absorption cross section and its reprocessing process is relatively easy. The U-7Mo/Al alloy is able to maintain the γ-U phase during irradiation process so that the stability of the fuel in the reactor is maintained. The U-7Mo alloy has been fabricated into a U-7Mo/Al mini fuel element plate. The purpose of this study was to determine the thermal characteristics of U-7Mo/Al as inputs to the research reactor fuel fabricator in the manufacture of UMo/Al-based fuel. Thermal characterization was carried out for uranium, molybdenum, UMo and the fuel element plate of U-7Mo/Al using Differential Scanning Calorimetry (DSC). The thermal characterization results show that the U-7Mo/Al fuel element plate is thermally stable up to 600 °C because it undergoes an endothermic thermochemical reaction at a temperature of 632.962 °C with DH = 144.318 J/g. At 656.186 °C, the Al matrix and AlMg2 cladding are fused in the U-7Mo/Al with DH = 144.318 J/g. At temperatures of 952.810 °C to 1106.050 °C, the molten Al matrix diffuses with UMo to form a metastable U(Mo,Al)X compound and heating to a temperature of 1211.760 °C forms a UAlX layer (UAl2, UAl3 and UAl4) with DH = –22,721 J/g.